Secretion of the human parathyroid hormone through a microcin type I secretion system in Escherichia coli - Flórez Cardona, Valeria (2024)
Background: Gram negative bacteria possess different secretion systems to export proteins to the extracellular medium. The simplest one, type I secretion system (T1SS), forms a channel across the cell envelope to export proteins in a single step. Peptides secreted by the T1SSs comprise a group of antibiotics, called class II microcins, which carry an amino terminal secretion domain that is processed concomitantly with export. Mature microcins range in size from 60 to 90 amino acids and differ in their sequences. Microcin T1SSs show a high versatility in relation to the peptides they are able to secrete, being mainly limited by the length of the substrates. Different bioactive peptides unrelated to bacteriocins could be secreted by microcin V (MccV) T1SS, while retaining their biological activity. Results: In this work heterologous secretion of two variants of human parathyroid hormone (PTH) by MccV T1SS was evaluated. PTH is a bioactive peptide of 84 amino acids (PTH84), which is involved in the maintenance of bone homeostasis. Currently, a drug corresponding to the active fraction of the hormone, which resides in its first 34 amino acids (PTH34), is commercially produced as a recombinant peptide in Escherichia coli. However, research continues to improve this recombinant production. Here, gene fusions encoding hybrid peptides composed of the MccV secretion domain attached to each hormone variant were constructed and expressed in the presence of microcin T1SS in E. coli cells. Both PTH peptides (PTH34 and PTH84) were recovered from the culture supernatants and could be confirmed to lack the MccV secretion domain, i.e. microcin T1SS efficiently recognised, processed and secreted both PTH variants. Furthermore, the secreted peptides were stable in the extracellular medium unlike their unprocessed counterparts present in the intracellular space. Conclusion: The successful secretion of PTH variants using MccV T1SS could be considered as a new alternative for their production, since they would be recovered directly from the extracellular space without additional sequences. Furthermore, it would be a new example revealing the potential of microcin type I secretion systems to be conceived as a novel strategy for the production of recombinant peptides in E. coli.